Handling semantic repetition when translating Arabic short stories: the case of Excerpt from The Book of The Dead - Al-Adwan, Amer; Abuorabialedwan, Mamon (Penerbit Universiti Kebangsaan Malaysia, 2019)
The translation of literary texts into another language is undoubtedly a challenging task, especially when dealing with a combination of languages that are linguistically, stylistically and culturally different. The main purpose of this paper is to examine the translation of one of the devices of creative writing used in the construction of Arabic short stories, namely semantic repetition. The analysis is based on comparing the occurrences of semantic repetition in the Arabic short story "ّذُمنا بارك هم ححفص" Excerpt from The Book of The Dead with their translations in the target text. This literary work, by Ahmad Faqih, has been selected for analysis mainly because it contains a significant number of repetition instances that serve various pragmatic functions. The main concepts and aspects of Toury’s theory of norms and other taxonomies of translation strategies will be used to identify translation shifts and strategies adopted by the translators. The analysis reveals that the translators resorted to four main strategies when translating semantic repetition into English: retention, compression, grammatical shift and deletion. The analysis also reveals that instances of semantic repetition are often omitted or modified in the English translation, and consequently their functions are sacrificed. This will certainly affect the representation of the original literary work and offer the target readers a slightly different version of the text.